2002
DOI: 10.1590/s1519-566x2002000300010
|View full text |Cite
|
Sign up to set email alerts
|

Teste de Vôo como Critério de Avaliação da Qualidade de Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae): Adaptação de Metodologia

Abstract: Embrapa Milho e Sorgo, C. postal 151, Sete Lagoas, MG 6 EMBRAPA/ EMPARN, C. postal 188, Natal pretiosum, kept in the laboratory for 3, 35 and 72 generations. Both models showed no difference in the quality of the studied populations, based on the percentage of parasitoids that showed initial flight activity after emergence. The ESALQ model allowed better discrimination between "non-flyers" and "flyers". Second, we monitored the quality of three sexual populations of T. pretiosum, started with one, five an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1
31

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 4 publications
0
22
1
31
Order By: Relevance
“…These tubes, containing the parasitoids, were then closed, and T. remus parasitism was allowed for 24 h. Adults emerging from these eggs were used for experiments or for colony maintenance. Quality control of the parasitoid colony was evaluated in accordance with Prezotti et al (2002) who performed each 10 generations of the insect, and endogamy issues were never observed.…”
Section: Parasitoid and Host Coloniesmentioning
confidence: 99%
“…These tubes, containing the parasitoids, were then closed, and T. remus parasitism was allowed for 24 h. Adults emerging from these eggs were used for experiments or for colony maintenance. Quality control of the parasitoid colony was evaluated in accordance with Prezotti et al (2002) who performed each 10 generations of the insect, and endogamy issues were never observed.…”
Section: Parasitoid and Host Coloniesmentioning
confidence: 99%
“…However, there are reports indicating that insect quality can be measured with a smaller number of parameters and in an easier way. Prezotti et al (2002) reported that longevity, parasitism and flight capacity were enough as indicators of the insect quality in rearing systems for these egg parasitoids. Furthermore, Prezotti et al (2004) reported the number of founding females of Trichogramma can be very low, without any lost in quality during continuous rearing.…”
Section: Constraints In the Mass Rearing Of Natural Enemiesmentioning
confidence: 99%
“…As taxas de parasitismo e de emergência, progênie, ciclo de desenvolvimento, longevidade de machos e largura da cápsula cefálica de fêmeas e machos de T. diatraeae, emergidos de pupas do hospedeiro natural D. saccharalis, foram semelhantes, após três gerações em pupas do hospedeiro alternativo T. molitor, não tendo, assim, comprometido a qualidade biológica deste parasitoide. A qualidade de um parasitoide é determinada por um conjunto de características biológicas (Roitberg et al 2001, Prezotti et al 2002, incluindo as avaliadas neste trabalho.…”
Section: Methodsunclassified